[18F]PARPi Imaging Is Not Affected by HPV Status In Vitro. (20th January 2021) - Guru, Navjot; Demétrio De Souza França, Paula; Pirovano, Giacomo; Huang, Cien; Patel, Snehal G.; Reiner, Thomas
Abstract : Background . Human papillomavirus- (HPV-) associated oropharyngeal squamous cell carcinomas (OPSCCs) are clinically and pathologically distinct from HPV-negative tumors. Here, we explore whether HPV affects functional biomarkers, including γ H2AX, RAD51, and PARP1. Moreover, the role of [ 18 F]PARPi as a broadly applicable imaging tool for head and neck carcinomas is investigated. Methods . HPV-positive and HPV-negative cell lines were used to evaluate the γ H2AX, RAD51, and PARP1 expression with immunoblotting and immunofluorescence. Effects of external beam ionizing radiation were investigated in vitro, and survival was investigated via colony-formation assay. [ 18 F]PARPi uptake experiments were performed on HPV-negative and HPV-positive cell lines to quantify PARP1 expression. PARP1 IHC and γ H2AX foci were quantified using patient-derived oropharyngeal tumor specimens. Results . Differences in DNA repair were detected, showing higher RAD51 and γ H2AX expression in HPV-positive cell lines. Clonogenic assays confirm HPV-positive cell lines to be significantly more radiosensitive. PARP1 expression levels were similar, irrespective of HPV status. Consequently, [ 18 F]PARPi uptake assays demonstrated that this tracer is internalized in cell lines independently from their HPV status. Conclusion . The HPV status, often used clinically to stratify patients, did not affect PARP1 levels, suggesting that PARP imaging can be performed in both HPV-positive and HPV-negative patients. This study confirms that the PET imaging agent [ 18 F]PARPi could serve as a general clinical tool for oropharyngeal cancer patients.